2019
DOI: 10.1007/s11214-019-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Magnetotail Activity

Abstract: Modes and manifestations of the explosive activity in the Earth’s magnetotail, as well as its onset mechanisms and key pre-onset conditions are reviewed. Two mechanisms for the generation of the pre-onset current sheet are discussed, namely magnetic flux addition to the tail lobes, or other high-latitude perturbations, and magnetic flux evacuation from the near-Earth tail associated with dayside reconnection. Reconnection onset may require stretching and thinning of the sheet down to electron scales. It may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 401 publications
(661 reference statements)
4
92
1
2
Order By: Relevance
“…Moreover, PIC simulations confirmed that the onset of fast dipolarization, including the spontaneous generation of fast earthward flows with the speed ∼ v A , may proceed very rapidly, consistent with observations, as long as the CS thickness is comparable to ρ 0 i . Furthermore, it was shown that the spontaneous dipolarization process leads, on the one hand, to the formation of dipolarization fronts, one of the most ubiquitous transient processes in the tail (e.g., Sitnov et al, , and refs. therein), and on the other hand, it naturally causes the formation of new X‐lines due to the flux starvation mechanism (Pritchett, ).…”
Section: February 13 2008 Substorms: Unsteady Reconnection and Non‐mmentioning
confidence: 99%
“…Moreover, PIC simulations confirmed that the onset of fast dipolarization, including the spontaneous generation of fast earthward flows with the speed ∼ v A , may proceed very rapidly, consistent with observations, as long as the CS thickness is comparable to ρ 0 i . Furthermore, it was shown that the spontaneous dipolarization process leads, on the one hand, to the formation of dipolarization fronts, one of the most ubiquitous transient processes in the tail (e.g., Sitnov et al, , and refs. therein), and on the other hand, it naturally causes the formation of new X‐lines due to the flux starvation mechanism (Pritchett, ).…”
Section: February 13 2008 Substorms: Unsteady Reconnection and Non‐mmentioning
confidence: 99%
“…During reconnection processes, the initially separated plasmas become magnetically connected, and the connected plasmas get ejected from reconnection region, producing high‐speed plasma flows, commonly referred to as reconnection jets or burst bulk flows (Angelopoulos et al, ; Cao et al, , ). Reconnection jets have been suggested to be responsible for energy dissipation, particle heating, and acceleration in space plasmas (e.g., Khotyaintsev et al, ; Fu et al, ; Lapenta et al, ; Lu, Angelopoulos, et al, ; Zhou et al, ; Sitnov et al, ; Chen, Fu, Liu, et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the exact mechanisms driving the magnetotail reconnection remain unresolved (Sitnov et al, 2019). Various theoretical models suggest that reconnection emerge spontaneously through tearing instability (Sitnov et al, 2013) or could be externally driven through forming a thin current sheet (Hesse & Schindler, 2001), for instance by increasing the lobe pressure or by current sheet bending (Kivelson & Hughes, 1990).…”
Section: Introductionmentioning
confidence: 99%